Contemporary linguodidactics of Ukrainian as a foreign language: achievements, problems, perspectives - Кушнір, І. (Teaching Languages at Higher Educational Establishments at the Present Stage. Intersubject Relations, 2019)
The author studies the formation of a relatively new branch of pedagogical science – linguodidactics of Ukrainian as a foreign language. The directions of development of this science are given by the changing requirements of modern society to the results of higher education and the communicative needs of the constantly changing contingents of educational migrants. The article focuses on the coordination measures that could provide rapid improvement of this science; the factors of development of teaching methods of Ukrainian as a foreign language are singled out. The modern linguistic and methodological paradigm and results of language education of foreigners of Ukrainian higher education institutions are described. Considerable theoretical and practical development of linguodidactics in the sphere of Ukrainian as a foreign one needs urgent renewal in connection with a significant reduction of classroom hours and an increase in the volume of independent work of students. Despite the aforementioned achievements in the development of linguistics of Ukrainian as a foreign language, there are a number of problems related to the lack of approval at the ministerial level of the regulatory elements of language education. Therefore, the study proposes a series of methodological and organizational actions that will influence the further development of linguodidactics of Ukrainian as a foreign language. The prospect of further research is the development of the system of approaches, with the introduction of an intensification principle at all its levels, and the creation of a mobile pluralistic model for teaching the Ukrainian language of various contingents of foreign applicants for the education at  Ukrainian higher education institutions.